Helper For A Food Waste Management Application - Moganesan, Veragu (2023)
Food is one of the most basic human needs and the most crucial component in human survival, however in today's world, food waste has become a serious worry. In recent years, food waste has become a topic of debate among the intellectuals and common people. Furthermore, a great number of people are affected by hunger. This is owing to the fact that a fraction of the population has financial difficulties in obtaining food on a daily basis. Moreover, many groups wish to request food but are unable to do so due to a lack of available resources. The goal of this research is to solve the food waste and hunger problem faced by people. By this project, an application named Helper for A Food Waste Management designed and developed. People can create an account and donate or request food using this application. For this project, the scrum methodology from the agile technique was used for the Software Development Life Cycle (SDLC). During the software development lifecycle, scrum methodology application development aids in the organization of design and planning, development, and testing processes. This project was developed in Java and built using Android Studio. The test cases conducted during the project's system testing phase to verify that any possible problems are identified. User Acceptance Testing (UAT) and Usability Testing were performed at the end of the project to ensure that the applications meet all of the project's requirements and specifications. 30 respondents who regularly donates food gives positive feedback to this application and they agree this application improved the food donation and food requests.